2008
DOI: 10.3327/taesj.j08.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen-to-Metal Ratio on Melting Temperature of Uranium and Plutonium Mixed Oxide Fuel for Fast Reactor

Abstract: The melting temperatures of uranium plutonium mixed oxide fuel for fast reactor were investigated as functions of Pu content, Am content, and oxygen-to-metal (O/M) ratio using the thermal arrest technique. Rhenium inner was used for the measurement to prevent the reaction between the sample and capsule materials. The solidus temperatures decreased with increasing Pu and Am contents and increased with decreasing O/M ratio. It is considered that the maximum temperature in the U Pu O system varies in the hypost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(5 reference statements)
1
8
0
Order By: Relevance
“…10,11) A model for solidus and liquidus temperatures was derived using the ideal solid solution model and it could represent those values in the hypostoichiometric composition range, which were needed for the development of fast reactor fuels. In this work, the range of application of the model was extended to the UO 2 -PuO 2 -Am 2 -NpO 2 -Pu 2 O 3 system by using the melting point of NpO 2 .…”
Section: Melting Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11) A model for solidus and liquidus temperatures was derived using the ideal solid solution model and it could represent those values in the hypostoichiometric composition range, which were needed for the development of fast reactor fuels. In this work, the range of application of the model was extended to the UO 2 -PuO 2 -Am 2 -NpO 2 -Pu 2 O 3 system by using the melting point of NpO 2 .…”
Section: Melting Temperaturesmentioning
confidence: 99%
“…[18][19][20] However, the physical properties of MOX containing 0-3% Am and 0-12% Np have been measured in recent studies, and it was found that the effect of Np and Am addition on the properties was small. [7][8][9][10][11][12][13][14][15][16][17] In this work, the physical properties of Np/Am-MOX were evaluated, and the irradiation behavior was analyzed by using those properties, which contribute to the development of the model for describing irradiation behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uranium and plutonium mixed oxide (MOX), having CaF 2 type fluorite structure, is nonstoichiometric compound with respect to the oxygen sublattice, and deviations from stoichiometry significantly affect on physical properties [1][2][3][4][5]. Therefore, it is essential to understand the oxygen potential, which is one of the important thermodynamics properties, as function of oxygen-to-metal (O/M) ratio, temperature and Pu content for development of MOX fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Stoichiometry significantly affects physical properties such as lattice parameters, oxygen potentials and melting temperatures [1][2][3][4]. Therefore, it is important to understand the characterictics of the defects in the non-stoichiometric composition for evaluation of the physical property change of PuO 2-x .…”
Section: Introductionmentioning
confidence: 99%